Od linearnej do cyrkularnej komunikacji literackiej, a stąd do milczenia (O sytuacji we współczesnych doktrynach literackich) - Erazm Kuźma (Przestrzenie Teorii)
This paper is a part of a whole which will be published later in a book. The first section concerns ambiguities of contemporary terms: "communication", "literature", "literary communication". The second part is devoted to the turn from linearity to circularity in the philosophy of Jaspers and Heidegger. The third part - to the same turn in sociology of Habermas and Luhmann. The fourth part - not included here - examins the turn to circularity in hermeneutics, Marxism, structuralism and deconstruction. The last part contains the outlook on the future of literary theory and literary scholarship.